Metastatic Squamous Cell Carcinoma with an Impending Femoral Neck Fracture: A Case Report. Issue 3 (July 2021) - Hull, Jonathan; Balsamo, Luke; Gibson, David
Abstract : Case: A 57-year-old man presented with a soft-tissue neck mass that has been present for 3 weeks. The patient is a former smoker. A biopsy of the mass confirmed squamous cell carcinoma (SCC). A positron emission tomography scan indicated metastatic disease in the patient's left femur. An impending pathologic fracture of the left femoral neck was evident. Discussion: The global incidence of oral SCC is increasing. Metastatic disease occurs rapidly with SCC. It is important for those practicing in orthopaedics to understand the aspects of this disease. This case review discusses the importance of understanding the rapid progression of metastatic SCC.